Minimally invasive surgical treatment in patients with immunological thrombocytopenic purpura: total splenectomy by a hybrid mini-laparoscopic technique - Carvalho, Gustavo Lopes de; Lima, Diego Laurentino; Cordeiro, Raquel Nogueira; Góes, Gustavo Henrique Belarmino de; Lessa, Marianna Castro Araújo (Revista de Medicina, 2020)
Two female patients, one 28 years-old, and the other 61 years-old, with a history of asthenia, purpura and thrombocytopenia (both <15,000 platelets / mm3). Once other etiologies were excluded, and the diagnosis of immune thrombocytopenic purpura (ITP) was established, corticoid therapy was started in both cases. However, the patients remained with a platelet count <20,000 / mm3, characterizing refractory ITP, and the splenectomy was indicated. The surgical team opted for a hybrid minimally invasive surgical procedure. Providing a better visualization of the surgical field, less abdominal trauma, greater technical dexterity, and early hospital discharge, the use of minilaparoscopic instruments proved to be a safe and effective approach for these patients.